Action prediction during real‐time parent‐infant interactions. Issue 3 (19th October 2020) - Monroy, Claire; Chen, Chi‐Hsin; Houston, Derek; Yu, Chen
Abstract: Social interactions provide a crucial context for early learning and cognitive development during infancy. Action prediction— the ability to anticipate an observed action—facilitates successful, coordinated interaction and is an important social‐cognitive skill in early development. However, current knowledge about infant action prediction comes largely from screen‐based laboratory tasks. We know little about what infants' action prediction skills look like during real‐time, free‐flowing interactions with a social partner. In the current study, we used head‐mounted eyetracking to quantify 9‐month‐old infants' visual anticipations of their parents' actions during free‐flowing parent–child play. Our findings reveal that infants do anticipate their parents' actions during dynamic interactions at rates significantly higher than would be expected by chance. In addition, the frequency with which they do so is associated with child‐led joint attention and hand‐eye coordination. These findings are the first to reveal infants' action prediction behaviors in a more naturalistic context than prior screen‐based studies, and they support the idea that action prediction is inherently linked to motor development and plays an important role in infants' social‐cognitive development. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=9HrmcicfiqE Abstract : We used mobile eye‐tracking to measure action prediction during a natural caregiver‐infant social interaction. We found that 9‐month‐old infants anticipate their parent's actions at rates higher than chance. This ability was correlated with joint attention and hand‐eye coordination, suggesting that action prediction is associated with skills that are central to infant social and cognitive development.